Urban Landscape in the Age of Reform: Salisbury, Bristol, Brighton, Lambeth, c.1820–1850 - Concannon, Amy (2019)
This thesis investigates the representation of urban places at a time of dramatic societal change in Britain. Unprecedented urbanisation, the polarising issue of political reform and major infrastructural change, epitomised by the ‘railway mania’ of the 1840s, served to re-map the British landscape. In this context, urban locales and their hinterlands were continuously redefined and endowed with new significances, thus offering new opportunities and challenges to those who took up the task of representing the urban landscape.